Effect of Particle Size and Solution Leaching on Water Retention Behavior of Ion-Absorbed Rare Earth - Zhong-qun Guo; Yuan-ming Lai; Jie-fang Jin; Jian-rong Zhou; Zheng Sun; Kui Zhao (Geofluids)
Soil-water characteristic curve reflects water retention behavior of unsaturated soil mass. Particle size and mineral composition can influence water retention behavior of soil mass significantly. To discuss effects of particle size and solution leaching on water retention behavior of ion-absorbed rare earth, soil-water characteristic tests of samples with different particle sizes before and after the solution leaching were carried out by using a pressure plate instrument. Soil-water characteristic curves during drying and wetting were analyzed. A fitting analysis on test data was implemented by the Fredlund&Xing 3 parameter model, the Fredlund&Xing 4 parameter model, and the Van Genuchten model to discuss variation laws of soil-water characteristic parameters in different models. Effects of particle size and solution leaching on water retention behavior of ion-absorbed rare earth as well as action mechanism were investigated. Results demonstrate that given the same matric suction, soil water content decreases gradually with the increase of particle size and content of coarse particles, thus decreasing water retention capacity of soil accordingly. Given the same volumetric water content, matric suction is inversely proportional to particle size. During drying and wetting, the amplitude of variation decreases gradually with the increase of particle size and content of coarse particles. The soil water content after solution leaching is smaller than that before under the same matric suction, indicating that solution leaching can decrease water retention capacity of soil. This is mainly because thickness of the double diffuse layer and pore water pressure are increased as a response to the ion exchange, thus decreasing matric suction.